Entelechy of the Emanational Form: Zenon Fajfer’s Poems of Potentiality - Bazarnik, Katarzyna (Przestrzenie Teorii, 2024)
Zenon Fajfer’s introduced into poetry an original, interactive form called “the emanational poem,” in which the multilevel acrostic is generative of simultaneously coexisting dimensions of text. The poet has used it in several of his works to render simultaneity, visibility and invisibility, potentiality and actuality. The article discusses the emanational form in view of Aristotle’s concept of entelechy. Exploring affordances of the electronic and printed media, the author explicates how the potentiality for mobility and intertextuality can be actualised in Fajfer’s “Ars Poetica,” Spoglądając Przez Ozonową Dziurę, and Powieki, drawing attention to the role of the reader in this process. She mentions the aporetic tension between the principle of Aristotelian entelechy and postmodern concept of intertextuality, also referencing the relevance of Ned Rossiter’s network theory to the interpretation of Fajfer’s work. Focusing on Powieki, a multimodal cycle of emanational poems, published as a compound of the material book and the digital poems in the CD, the author postulates, following Pisarski (2014) and Marecki (2018), that it is an entelechy of the hypertext. Moreover, this richly hyperlinked cycle of poems can be seen as a rewriting of the Orphean katabasis. It invites contem- plation of a complex, multidimensional space that should be explored in “slow,” or close reading, which defies typical expectations of electronic literature audiences. Finally, it is argued that Fajfer’s print-born digital hypertexts activate potentialities entailed in the matter(iality) of the writing in both media, the old and the new.